Risk of serious opportunistic infections after solid organ transplantation: interleukin-2 receptor antagonists versus polyclonal antibodies. A meta-analysis. Issue 7 (July 2014) - Kalil, Andre C; Florescu, Marius C; Grant, Wendy; Miles, Clifford; Morris, Michael; Stevens, R Brian; Langnas, Alan N; Florescu, Diana F
Abstract : Background: We aimed to evaluate and quantify the risk of serious opportunistic infections after induction with polyclonal antibodies versus IL-2 receptor antagonists (IL-2RAs) in randomized clinical trials. Methods: PRISMA guidelines were followed and random-effects models were performed. Results: 70 randomized clinical trials (10, 106 patients) were selected: 36 polyclonal antibodies (n = 3377), and 34 IL-2RAs (n = 6729). Compared to controls, polyclonal antibodies showed higher risk of serious opportunistic infections (OR: 1.93, 95% CI: 1.34–2.80; p < 0.0001); IL-2RAs were associated with lower risk of serious opportunistic infections (OR: 0.80, 95% CI: 0.68–0.94; p = 0.009). Polyclonal antibodies were associated with higher risk of bacterial (OR: 1.58, 95% CI: 1.00–2.50; p = 0.049) and viral infections (OR: 2.37, 95% CI: 1.60–3.49; p < 0.0001), while IL-2RAs were associated with lower risk of cytomegalovirus (CMV) disease (OR: 0.73, 95% CI: 0.56–0.97; p = 0.032). Adjusted indirect comparison: compared to polyclonal antibodies, IL-2RAs were associated with lower risk of serious opportunistic infections (OR: 0.41, 95% CI: 0.34–0.49; p < 0.0001), bacterial infections (OR: 0.51, 95% CI: 0.39–0.67; p < 0.0001) and CMV disease (OR: 0.58, 95% CI: 0.34–0.98; p = 0.043). Results remained consistent across allografts. Conclusion: The risk of serious opportunistic infections, bacterial infections and CMV disease were all significantly decreased with IL-2RAs compared to polyclonal antibodies.